The role of microbiota in autism spectrum disorder: A bibliometric analysis based on original articles - Lin, Xiaoling; Zhou, Runjin; Liang, Dandan; Xia, Lingling; Zeng, Liying; Chen, Xiaogang (Frontiers in Psychiatry, 2022)
Background Gastrointestinal (GI) symptoms can be observed in autism spectrum disorder (ASD) children. It is suggested that the gut microbiota and its metabolites are associated, not only with GI symptoms, but also with behaviors of ASD. The aim of this study was to explore the development context, research hotspots and frontiers of gut microbiota and ASD from January 1, 1980 to April 1, 2022 by bibliometric analysis. Materials and methods Publications of ASD and gut microbiota research from 1 January 1980 to 1 April 2022 were retrieved from the Web of Science Core Collection (WoSCC). Publications and citations trends were analyzed by Excel 2010. CiteSpace was used to analyze countries/regions, authors, institutes, references, and keywords and to visualize the knowledge map. Results A total of 1027 studies were retrieved, and 266 original articles were included after screening. The most published countries and institutes were the United States and King Saud University. Afaf El-Aansary published the most articles, while Finegold SM had the highest co-citations. Hotspots and emerging trends in this area may be indicated by co-cited references and keywords and their clusters, including “gut-brain axis,” “behavior,” “chain fatty acid,” “brain,” “feces,” “propionic acid,” “clostridium perfringens,” and “species clostridium innocuum.” Conclusion The United States dominants the research in this field, which focuses on the alterations of gut microbiota composition and its metabolites, among which the roles of the genus Clostridium and metabolites of short-chain fatty acids, especially propionic acid, are priorities. Fecal microbiota transplantation (FMT) is a promising complementary therapy. In general, research in this area is sparse, but it still has great research prospects.